Propuesta de redistribución de planta y su efecto en la productividad, en el taller de maestranza-turbinas de la empresa Agroindustrias San Jacinto s.a.a. - Céspedes Baca, Pablo Antonio (2016)
This research has the main objective to determine the influence that proper relocation of Maestranza-turbines workstations has on productivity of the factory of Agroindustrias San Jacinto S.A.A. The methodology used in the research was descriptive, so the research focused on the collection and analysis of information in this way, propose a solution to the problem encountered in the factory. The sample for the study was the selected process productivity maintenance performed during the study period. The investigation began with a diagnosis of the current situation in the factory, highlighting the deficiencies observed. Looking up the SAP system, the list of products manufactured by the factory in the study period was obtained. Then it was identified production lines, linking products with equipment used. Since not all lines have the same production capacity, it was selected the most important by a Pareto chart, determining that only 7 are those representing approximately 80% of the work area. In addition, the list of productive resources of factory was described. With this information, the redistribution under the guidelines of Systematic Layout Planning was designed. Thus, using the Muther methodology, new workstations and flowcharts were defined together for the relationship diagram. Subsequently Guerchet methodology was applied to determine the recommended stations each size. Realizing iterations, it was able to design two alternatives, of which the best was chosen by assessing factors. With the proposed redeployment was estimated to result in increased productivity by partial indicator of the productivity of human input. The result showed an increase shop productivity at 15.24%, from an index of 0.984 to 1.134 if it can implement the proposal. Finally the economic evaluation was performed, where the project's viability was determined after obtaining a NPV of S/.21138.85, an IRR of 3.80% and a B/C 1.25